Development of emotions and emotion regulation - Holodynski, Manfred 1957-; Friedlmeier, Wolfgang 1960- (Springer, 2005)
While there are many standard theories of the origin and purpose of emotions, Development of Emotions and Emotion Regulation departs from traditional viewpoints to offer new and provocative insights
Keywords: Développement affectif; Développement de la personnalité; Emoties; Emotionele ontwikkeling; Psychologie du développement; Régulation (Psychologie); Émotion; Émotions; Emotions; Developmental psychology; Entwicklungspsychologie; Affektive Entwicklung; Emotionales Verhalten; Gefühl